Factors influencing audit opinion going concern - Ahmad Faishal Hanif; Firda Ayu Amalia; Agung Prasetyo Nugroho Wicaksono (DINASTI RESEARCH, 2023)
This study was conducted to investigate the impact of company size, audit tenure, financial distress, and audit quality on going concern audit opinions on all sectors of companies listed on the Indonesia Stock Exchange (IDX), except the financial sector in 2019–2021. The sample consisting of 153 companies was selected using purposive sampling techniques, i.e., companies were selected based on certain considerations. The sample of 153 companies was then analyzed using the logistic regression method and assisted by Eviews 10 software. The results in this study are company size, audit tenure, financial distress, and audit quality have no influence on going concern audit opinion.